Pertumbuhan Laba Dilihat dari Green Banking dan Kredit Macet pada Perbankan yang Terdaftar di Bursa Efek Indonesia - Ni Luh De Erik Trisnawati; Ni Komang Sukreni (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the effect of green banking, bad debts on profit growth. This study uses secondary data and time series conducted on banking sector companies listed on the Indonesia Stock Exchange from 2022 to 2024. This study uses a quantitative approach. The population in this study were banking companies listed on the Indonesia Stock Exchange, totaling 12 companies. Based on the results of the analysis that have been explained in the path coefficients table, it is known that the effect of green banking on profit growth is positive and insignificant where the original value of the calculated t value is 1.054 <t table 2.032 with a p-value or significant value of 0.142> 0.050, which shows that the first hypothesis that green banking has an effect on profit growth in banking listed on the IDX is rejected. Based on the results of the analysis that have been explained in the path coefficients table, it is known that the effect of bad debt on profit growth is positive and insignificant where the calculated t value is 1.648 <t table 2.032 with a p-value or significance of 0.109> 0.050, where this shows that the second hypothesis which says that bad debt has an effect on profit growth in banking listed on the IDX is rejected.